Survey of application of machine learning in wireless channel modeling - Liu LIU; Jianhua ZHANG; Yuanyuan FAN; Li YU; Jiachi ZHANG (Tongxin xuebao)
Channel characterization is primary to the design of the wireless communication system.The conventional channel characterization method cannot learn the law of certain types of channels by itself, which limits its application in several special scenarios, such as Internet of things, millimeter wave communication and Internet of vehicles.Machine learning was able to process the big data and establish the model.Based on this, the cooperation between the machine learning and channel characterization was investigated.The channel multipath clustering, parameter estimation, model construction and wireless channel scene recognition were discussed, and recent significant research results in this field were provided.Finally, the future direction of the machine learning in wireless channel modeling was proposed.